Effects Of Pineapple Consumptions On Sensory Perceptions, Somatosensation And Taste Threshold - Romli, Siti Rashima (2023)
This study aims to determine the effects of pineapple consumptions on sensory perceptions, somatosensation, and taste threshold. The acceptance and consumption of pineapples among consumers were surveyed, and physicochemical and sensory acceptance of three pineapple varieties planted in the northern part of peninsular Malaysia (Moris, N36, and MD2) at various maturity stages were determined. The survey was conducted online with 167 respondents using a self-administrated questionnaire. A total of 28.1% of respondents refuse to eat pineapple because it causes an unpleasant feeling on the tongue (61.7%) and affects taste sensation (19.1%) after consumption. Although consuming fresh pineapple causes tongue irritation, consumers still prefer fresh fruit (61%) over processed pineapple due to its vitamin C, fibres, and bromelain enzyme, as well as its appealing flavour. Principal component analysis (PCA) plot with 80.16% variance shows that physicochemical properties such as lightness (L value), textures, titratable acidity, and vitamin C are important factors that influence consumer acceptance of the fruit. Pineapples harvested at Index 4 and Index 5 are suitable for fresh fruit consumption due to the texture and sensory acceptance of the fruit. Moris and N36 pineapples are nearly identical (>80% similarity) in terms of physicochemical properties and consumer acceptance, whereas MD2 has distinct organoleptic qualities such as being sweeter, less acidic, higher in vitamin C and more aromatic compared to Moris and N36.